Understanding “Recovery” Following Ankle Reconstruction: A Qualitative Study - Ellie Pinsker BA&Sc, PhD(cand.); Monique A.M. Gignac PhD; Joanna E.M. Sale PhD; Timothy R. Daniels MD, FRCSC; Dorcas E. Beaton PhD (Foot & Ankle Orthopaedics, 2019)
Category: Ankle, Ankle Arthritis, Outcomes research Introduction/Purpose: Patients’ perception of a good outcome (‘feeling recovered’) is not fully understood. A clear understanding of the benefits and harm of a surgery is necessary for clinical decision-making. Qualitative work exploring the nature of patient recovery would improve our ability to understand and measure these outcomes. The purpose of the study is to examine patients’ perceptions of post-surgical outcome following ankle reconstruction for treatment of end-stage ankle arthritis. Methods: Twenty-five English-speaking individuals were asked to participate following a routine clinic visit. They were recruited from an existing cohort of persons who had undergone total ankle replacement or ankle fusion at least one year prior. A qualitative researcher conducted semi-structured, face-to-face interviews with participants in a private hospital room. Results: Twenty-five adults (12 women, 13 men) ages 25–82 years were interviewed for 1-2 hours. Participants varied in their socioeconomic status and education levels. Patients did not view their recovery simply as physiological change. Most participants reported ongoing challenges or difficulties, yet considered themselves better. Participants described a broader concept of recovery with multiple contributing factors, including appraisal of the importance of ongoing issues and coping efforts. When participants experienced ongoing difficulty with valued activities, they gained a sense of recovery using coping efforts. Many ‘readjusted’ behaviorally to continue with their valued goals and activity preferences. Others cognitively redefined their goals or preferences to accommodate their ongoing issues. Participants who could not cope with their difficulties or disliked their coping effort perceived their recovery negatively. Conclusion: Perception of recovery and experience of outcome rarely involved resolution of all symptoms and functional limitations. The manner in which patients described their recovery was typically more nuanced than a simple change in magnitude of symptoms or functional limitations. This research expands our understanding of the experience of ankle reconstruction and draws attention to different meanings of recovery that has implications for outcome evaluation and measurement. Improved measures for evaluating the recovery outcome states will enable clinicians to identify facilitators and barriers to recovery.